Gambling disorder gender analysis: social strain, gender norms, and self-control as risk factors - Man, Pui Kwan (Frontiers in Sociology, 2024)
IntroductionGender differences in problem gambling have attracted much attention in recent gambling literature. However, relatively little is known about how gender norms relate to social strain and self-control in predicting gambling disorder within a spousal context. This study aimed to increase knowledge about gambling disorder in Chinese married couples by assessing the three-way interaction effects between social strain, self-control, and gender norms.MethodsA total of 1,620 Chinese married couples were recruited from a representative sample of households in Hong Kong.ResultsThe results of the generalized ordered logit model revealed the self-control mitigation effect of composite strain on the propensity for gambling disorder is strong in men who accept traditional gender norms. In contrast, in women who accept traditional gender roles, self-control attenuates the effect of recent stressful life events on the propensity for gambling disorder, but self-control exacerbates the effect of negative relationships with offspring on the propensity for gambling disorder.DiscussionAlthough reinforcing self-control is a protective factor that can alleviate social strain and disordered gambling for both men and women, the prominent contribution of gender norms to the self-control exacerbation effect deserves close attention for social workers who provide services to these gambling families.